"An Independent Little Sausage": Sexual Agency and Desire On Dearborn Street. Issue 1 (2nd January 2021) - Lee, Janet
Abstract: In the teeming public space of modern U.S. cities at the end of the long nineteenth century, New Women carved out a place for themselves and navigated the opportunities and constraints associated with love and vocation on the eve of war. I address these representations, and focus on sexual agency and desire through the lens of Australian feminist Stella Miles Franklin's New Woman novel, On Dearborn Street. I examine Franklin's portrayals of a nuanced and somewhat contradictory sexual self-determination influenced by her personal and political life in Chicago, and emphasise the ways the novel resists romance narratives by refusing the choice between marriage and independence.